Multi-criteria assessment of sustainability of construction objects using the TOPSIS method - Ustymenkо Andrii (Ways to Improve Construction Efficiency, 2025)
The modern development of the construction industry takes place in conditions of increasing requirements for environmental responsibility, energy efficiency, social orientation and safety of construction objects, which actualizes the need to form scientifically based approaches to assessing their sustainability. Existing certification systems for sustainable construction, although they play an important role in the implementation of "green" standards, are mainly normative in nature and do not always provide the flexibility and analytical versatility necessary for the comparative analysis of alternative construction projects in the process of making management and investment decisions. In this regard, the importance of developing integrated sustainability assessment models adapted to the life cycle conditions of construction objects and focused on innovative development of the industry is increasing.The aim of the article is to develop and substantiate a methodological approach to assessing the sustainability of construction sites based on a multi-criteria model using the TOPSIS method. As part of the study, a system of sustainability assessment criteria was developed, which covers six key groups: resource and environmental efficiency, economic and innovative sustainability, socially functional quality, life cycle and adaptability, safety of the construction site, as well as management quality and ESG orientation. For each criterion, weighting coefficients were determined that reflect their relative importance in ensuring the sustainable development of construction sites. An integral indicator of the sustainability of a construction site was proposed, which is calculated as a weighted sum of the criteria scores, and a scale for interpreting the results, which allows classifying sites by the level of sustainability - from low to innovatively sustainable. The TOPSIS method was used to perform a comparative assessment of alternatives, which provides a determination of the degree of proximity of each site to a conditionally ideal sustainable solution and its distance from an anti-ideal state.The practical applicability of the proposed approach was demonstrated by testing the model on the example of residential complexes, which allowed them to be ranked by the level of sustainability and to identify key factors that most affect the increase or decrease in the integral indicator. The results obtained confirm that the proposed model is an effective analytical tool for a comprehensive assessment of the sustainability of construction objects and can be used in the practice of development, investment analysis and construction project management.The scientific novelty of the study lies in the formation of a comprehensive system of criteria for assessing the sustainability of construction objects with an emphasis on safety and ESG-oriented management, as well as in the application of the TOPSIS method as a tool for integrated assessment within the framework of an innovation-oriented model of sustainable development.